Enhanced anticancer effect of quercetin microparticles formulation obtained by spray drying. (5th January 2022) - Caruana, Roberto; Montalbano, Francesco; Zizzo, Maria Grazia; Puleio, Roberto; Caldara, Gaetano; Cicero, Luca; Cassata, Giovanni; Licciardi, Mariano
Abstract: This study unravels a formulation made of food‐based microparticles (MPs) able to control the release of quercetin, a natural anticancer compound, which activity is only limited by its poor aqueous solubility and consequent low bioavailability. To solve this issue, a spray‐dried micro delivery system was developed using a bench mini spray dryer B290 Buchi. The resulting MPs were only manufactured with food‐derived ingredients such as whey proteins and milk, avoiding the use of any other synthetic material. These microparticles were characterised with a testing campaign encompassing either the physical–chemical characterisation with SEM, DSC and DLS, or the technological and biological features with in vitro, ex vivo and in vivo studies, the latter being characterised by a human colon cancer xenograft model. These studies showed as the quercetin solubility and release rate improved when tested in condition mimicking oral administration, resulting in a general improvement of its bioavailability and the consequent anticancer activity. This study shows as the whey proteins may serves as natural adjuvant able to provide valuable technological features when used to manufactures micro carriers by spray drying. Abstract : Multiple oral administration of quercetin embodied in the microparticles prevents the tumour mass from increasing in volume compared to pure quercetin.